Combination of White Blood Cell Count to Mean Platelet Volume Ratio and Neutrophil-to-Platelet Ratio Predicts Long-Term Adverse Events in Patients with MINOCA - Ayman A. Mohammed; Lu Liu; Redhwan M. Mareai; Abdul-Quddus Mohammed; Guoqing Yin; Shekhar Singh; Yawei Xu; Fuad A. Abdu; Wenliang Che (Hindawi Limited, 2022)
Background. White blood cell count to mean platelet volume ratio (WMR) and neutrophil-to-platelet ratio (NPR) have been demonstrated as prognostic inflammatory biomarkers of the acute coronary syndrome. We aimed to evaluate the prognostic value of WMR and NPR among myocardial infarction with nonobstructive coronary arteries (MINOCA) patients. Method. A total of 274 MINOCA patients were enrolled. Baseline clinical data, blood cell panel, and biochemical parameters were evaluated. The patients were classified according to the medians of WMR and NPR. The primary endpoint of the present study was major adverse cardiovascular events (MACE). Multivariable Cox regression analysis was used to assess the effect of independent variables of WMR and NPR on the dependent variable (MACE). Result. The median values of WMR and NPR were 701 and 0.03, respectively. During the median follow-up of 28 months, a total of 58 incidences of MACE occurred. The MACE rate was more frequent in high WMR and high NPR patients. In Kaplan-Meier analysis, the incidence of MACE was higher in WMR>701 and NPR>0.03 (long-rank P=0.004 and P=0.002, respectively). The combined high WMR and high NPR showed a significantly higher rate of MACE (long-rank P=0.001). Cox regression analysis showed that the combined high WMR and high NPR were independent predictors of long-term MACE with the highest hazard ratio (HR, 2.511; 95% CI, 1.271 to 4.960; P=0.008). Conclusion. High WMR and NPR separately or in combination were correlated with increased risk of MACE among MINOCA patients, suggesting WMR and NPR may assist as a reliable inflammatory marker in risk prediction of MINOCA patients.